What drives MSME performance? The role of gender, operational aspects, and social environment - Prayudi, Made Aristia; Vijaya, Diota Prameswari; Ekawati, Luh Putu (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2019)
This study aims to investigate the effect of gender toward the ease of access to capital, entrepreneurial behaviour, and the performance of MSMEs. In contrast to previous studies, this research is also testing the moderating effect of the patriarchy on the relationship between gender and the variables of interest. Data were collected using a self-administered questionnaire distributed to 201 MSME entrepreneurs throughout Bali Province of Indonesia and analysed using a partial least square structural equation modelling (PLS-SEM) technique. Results indicated that (1) female entrepreneurs of MSMEs have a lower level of perceived ease of access to capital; (2) patriarchy positively moderates the relationship between gender and the ease of access to capital; (3) female entrepreneurs of MSMEs have lower performance than its counterparts; (4) entrepreneurial behaviour has a positive effect on MSMEs performance; and (5) the ease of access to capital have a positive impact on entrepreneurial behaviour.